Research on Neural Cells in Artificial Intelligence - Jamolova Gulbanbegim Muzaffar kizi (Scientific Trends, 2024)
This article provides information about the general classification and structure of artificial neural networks and the tasks they solve. The areas where artificial neural networks and their applications are used were also discussed.
Keywords: Artificial neuron, artificial intelligence, machine learning, artificial superintelligence, intellectual activity.